Determination of Hypericin Content in Flowers and Leaves of Eight Hypericum Species - K Jaimand; MB Rezaee; V Mozaffrian; R Azadi; M Naderi Haji Bagher Kandy; S Meshkyzadeh; M Golipoor (Institue of Medicinal Plants, ACECR, 2008)
Background: Hypericum genus is one of the most important medicinal plant that contains 17 species in Iran, three of them are endemic. Objective: In this research hypericin content of flowers and leaves of eight Hypericum specie was determined. Methods: Plant material was extracted with chloroform by Soxhlet until chlorophyll ceased extracting, after removal of chloroform, the thimble was re-extracted with methanol until the red pigment, hypericin, ceased extracting. The analysis of hypericin use of a reversed-phase high performance liquid chromatography (HPLC) method with UV detection on 590 nm. The mobile phase consisted of methanol 68%: ethyl acetate 20%: 0.1 M NaH2PO4.2H2O 12% and with column C18. Results: Identification of the compound was on extraction of 1 grams of flowers and leaves. Hypericin content obtained in H.dogonbadanicum (flower 36 and leaves 36 ppm) which are endemic, H. helianthemoides (flower 118 and leaves 22 ppm), H. hirtellum (flower 178 and leaves 26 ppm), H. hyssopifolium (flower 224 and leaves 120 ppm), H.lysimachioides (flower 1177 and leaves 178 ppm), H. perforatum (flower 1900 and leaves 813 ppm), H. scabrum (flower 13 and leaves 10 ppm) and H. triquetrifolium (flower 1460, leaves 1426 and stem 17 ppm). Conclusion: Hypericin content in different Hypericum show that are different, highest are in H. perforatum with 1900 ppm and in H. triquetrifolium with 1460 ppm.